Yield criteria in anisotropic finite elasto-plasticity - Cleja-Tigoiu, S. (Archives of Mechanics, 2005)
The paper deals with several descriptions of the yield criteria, within the constitutive framework of anisotropic finite multiplicative elasto-plasticity. We put into evidence appropriate yield criteria, defined either in stress or strain spaces and we analyse the Eulerian setting attached to Σ-models, first described in relaxed configuration, when Σ represents the Mandel's stress measure or the quasistatic Eshelby stress tensor. We compare our anisotropic model with the elasto-plastic model, usually adopted in computational finite plasticity.